Robust Camera Pose Estimation from Line Correspondences Using GNC - Hans K.R. Holen; Torbjørn Smith; Olav Egeland (Modeling, Identification and Control)
A solution to the Perspective-n-Lines (PnL) problem is proposed where a large fraction of outliers can be handled. The approach estimates camera pose from 2D-3D line correspondences where outliers are in the form of line mismatches. The solution is based on graduated non-convexity (GNC) with truncated least squares with Dynamical Pose Estimation (DAMP) as a solver. The solution is simple to implement and does not require specialized optimization software. The method is compared to 11 state-of-the-art PnL methods using synthetic and real data and evaluated in terms of accuracy, running time, and sensitivity to noise and outliers. The results show that our proposed method scores among the top for accuracy and robustness.